Etika Media Global: Tantangan Dan Peluang Di Era Digital - Ayu Trysnawati; Arifuddin Tike; Kamaluddin Tajibu (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
This study aims to analyze global media ethics in the digital era, specifically by identifying the various challenges and opportunities arising from advancements in communication technology. A qualitative method employing a library research approach was used, involving the search and analysis of scholarly literature via Publish or Perish (PoP) integrated with Google Scholar and Scopus. Analysis was conducted through data reduction, interpretation, and synthesis of relevant sources. The results indicate that key challenges in global media ethics include algorithmic dominance, rising disinformation, and social polarization that affects the quality of public communication. Conversely, strategic opportunities exist in the form of strengthened digital literacy, increased public participation, and the development of cross-sector collaborative regulations. These findings underscore the dynamic nature of global media ethics, necessitating an adaptive approach that integrates technological, policy, and user-awareness aspects. The study's implications are expected to serve as a foundation for developing more ethical media policies and strengthening responsible digital communication practices on a global scale.